2017
DOI: 10.1177/0165025417711057
|View full text |Cite
|
Sign up to set email alerts
|

Character development among youth

Abstract: This article embeds the study of character development within the two-decades-long research program framed by the Lerner and Lerner model of positive youth development. Character development involves attaining the feelings, thoughts, and skills needed to act coherently across time and place to serve self and others in mutually beneficial, positive ways. Research in the U.S. and other nations suggests that there are three key features of successful character development initiatives for children and adolescents:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 70 publications
(101 reference statements)
1
26
0
1
Order By: Relevance
“…Furthermore, the differential contribution of distinctive attitudinal dispositions (e.g., civic attitudes, altruistic orientation) when it comes to predicting CP profiles also remains unknown. Given that several specialists have previously theorized that individual attributes may be the most powerful predictors of civic identity among young adults (Vráblíková & Císař, 2015;Flanagan & Levine, 2010;Johnson et al, 2014;Lerner, 2018), it appeared essential to include these variables in our design. Finally, the predictive effects of the aforementioned contextual and individual attributes on CP profile membership have never been examined simultaneously within a single model.…”
Section: Conceptualization Of Civic Participation and Use Of Person-centered Analysesmentioning
confidence: 99%
“…Furthermore, the differential contribution of distinctive attitudinal dispositions (e.g., civic attitudes, altruistic orientation) when it comes to predicting CP profiles also remains unknown. Given that several specialists have previously theorized that individual attributes may be the most powerful predictors of civic identity among young adults (Vráblíková & Císař, 2015;Flanagan & Levine, 2010;Johnson et al, 2014;Lerner, 2018), it appeared essential to include these variables in our design. Finally, the predictive effects of the aforementioned contextual and individual attributes on CP profile membership have never been examined simultaneously within a single model.…”
Section: Conceptualization Of Civic Participation and Use Of Person-centered Analysesmentioning
confidence: 99%
“…Virtuous character encompasses behaviors, cognitions, and motivations that make a person a "moral agent" within their social world and allows a person to achieve the highest potential (Berkowitz & Bier, 2004;Cawley III, Martin, & Johnson, 2000;Lerner, 2017;Park, 2004). Virtuous character includes a wide range of behaviors, characteristics, and personality traits, including trustworthiness, empathy, and self-control.…”
Section: Virtuous Charactermentioning
confidence: 99%
“…These interventions, however, are only effective approximately half the time, with the lowest efficacy during adolescence (Berkowitz & Bier, 2007). In part, the modest efficacy of these interventions may be due to the lack of incorporating important parental behaviors during adolescence (Kasser, Ryan, Zax, & Sameroff, 1995;Lerner, 2017;Mahatmya & Lohman, 2012) and heritable influences (Knafo & Plomin, 2006b;Spengler, Gottschling, & Spinath, 2012;Zahn-Waxler, Robinson, & Emde, 1992) that shape the development of virtuous character behaviors. By examining both genetic and environmental influences on parenting and adolescent virtuous character behaviors as well as the pathways in which genetic and environmental influences contribute to their association, we will disentangle the underlying mechanisms driving these constructs and their association.…”
mentioning
confidence: 99%
“…Activity engagement research has extended from middle childhood and into the third decade of life, an age range in which PYD also applies (Lerner, 2018). Previously, researchers have found that different profiles of adolescents' sports participation and more frequent participation in a greater variety of activities were associated with overall PYD into late adolescence (Agans et al, 2014;Agans & Geldhof, 2012).…”
Section: Pyd and Activity Engagementmentioning
confidence: 99%